AGREEMENT OF MELBOURNE RAPID FIELDS PERIMETRY PARAMETERS TO HUMPHREY FIELD ANALYZER IN MODERATE-SEVERE GLAUCOMA PATIENTS: RELATIONSHIP BETWEEN VISUAL ACUITY AND MELBOURNE RAPID FIELDS ACCURACY: Oral Presentation - Observational Study - Resident - Mayasari, Yuri Dwi; Oktariana, Virna Dwi; Fitriani, Dewi Yunia (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives Perimetric examination is vital for measuring visual field defects and predicting the progression of glaucoma. The Covid-19 pandemic prompted the use of perimetry at home. Tablet or website-based perimetry becomes an option due to unavailability of Humphrey Field Analyzer (HFA). Melbourne Rapid Fields (MRF) is affordable, portable and reliable, even provide the same benefits as HFA. This study aimed to assess the agreement of MRF results to HFA in moderate-severe glaucoma patients with impaired visual acuity. Methods Observational study using a cross-sectional design to assess the relationship between visual acuity and the agreement of MRF vs HFA in moderate-severe glaucoma patients. Subjects were grouped into two groups based on visual acuity. Each subject was examined with MRF and HFA, the order of examination was randomized using block randomization. Results The test durations were shorter on MRF than HFA (265.7±26.6 vs 384.4±46.7, P<0.001). There was no significant difference in the reliability index of the two perimetry. MRF showed a high level of concordance in its outcomes with HFA (R=0.931, intraclass correlation coefficient (ICC)=0.957 for mean defect (MD) and R=0.941, ICC=0.974 for Visual Field Index (VFI)). MRF also showed levels of test-retest repeatability comparable to HFA (R=0.948, ICC=0.989 for MD and R=0.946, ICC=0.989 for Visual Capacity (VC)). There was no correlation between visual acuity and MRF accuracy, p>0.05. Conclusion The perimetry results from MRF have a very stong correlation to the HFA outcomes. MRF also has test-retest repeatability comparable to HFA. The accuracy of the MRF results does not correlate with visual acuity.